PENGUATAN DAYA SAING PENGUSAHA MIKRO SURAKARTA : REVOLUSI VISUAL MELALUI PELATIHAN FOTOGRAFI PRODUK - Sisca Dian Rahmawati; Febrianur Ibnu Fitroh Sukono Putra; Mahmud Mahmud; Awanis Linati Haziroh; Rina Wulandari (CV. Denasya Smart Publisher, 2024)
PCM Laweyan has trained entrepreneurs in various fields, including the service, trade, production/manufacturing, culinary, and consulting sectors. Along with developments in technology, information and communication, businesses under PCM Laweyan must adopt new approaches to their business activities according to market desires. The entrepreneurs assisted by PCM Laweyan must utilize digital marketing in their marketing process. This is useful for increasing turnover and expanding the business market fostered by PCM Laweyan. However, entrepreneurs assisted by PCM Laweyan experience difficulties getting the right information technology solutions and need clarification about finding the right solution from the many different types of technology products. Therefore, this service aims to guide the choice of the right information technology according to the type of business and its needs and optimize the technology used. This program covers three areas: information and technology, marketing management, and HR management. The methods applied are training, mentoring, monitoring, and evaluation. The results of this service program can be seen from the changes on social media and MSMEs' websites after training and mentoring. Their promotional content becomes more attractive and professional, reflecting the impression of professionalism and quality of the products offered. This service program has helped increase the attractiveness of MSME businesses in the wider market through social media and e-commerce platforms.